1992
DOI: 10.1002/tea.3660290506
|View full text |Cite
|
Sign up to set email alerts
|

Children's conceptions of color

Abstract: An examination of children's notions about light and visual phenomena shows the existence of mental models, that is to say, ways of thinking that are consistent and pervasive. These naive conceptual schemes, used by different children to explain similar phenomena, determine the kinds of responses given by the children in problem-solving situations. In this article we study children's ideas about colored objects and colored shadows, with special attention to the ways in which these ideas are organized into ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
7

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 9 publications
3
32
0
7
Order By: Relevance
“…Researchers interested in what information has been learnt, at the learning end of the curiosity/learning continuum, have included Griffin and Symington (1997), McClafferty (1995), Borun et al (1993) and Feher and Meyer (1992). Almost every one of these studies used a pre-and post-test and showed from the scores, that in most cases good results depended on previous learning, formal or naive.…”
Section: Research At Vista and Other Science Centresmentioning
confidence: 97%
“…Researchers interested in what information has been learnt, at the learning end of the curiosity/learning continuum, have included Griffin and Symington (1997), McClafferty (1995), Borun et al (1993) and Feher and Meyer (1992). Almost every one of these studies used a pre-and post-test and showed from the scores, that in most cases good results depended on previous learning, formal or naive.…”
Section: Research At Vista and Other Science Centresmentioning
confidence: 97%
“…Previous research about the colour phenomena already has established that children's ideas about colour are organized in coherent and systematic ways (Feher & Meyer, 1992). A detailed analysis of the misconceptions allowed us to categorize them into different qualitative levels and formulate five variants of students' representations of colour phenomena (Table 3).…”
Section: Students' Internal Representations Of Colour Phenomenamentioning
confidence: 99%
“…Chauvet, 1996;Feher & Meyer, 1992;Osborne et al, 1993;Viennot, 2002;Woolf, 1999). Table 1 shows the most frequent ideas students have about colour phenomena (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The intention was to investigate an underdeveloped concept area in the school syllabus, that of colour. Colour was chosen since although it would appear to be important and of relevance in all science subjects, very little has been written about children's ideas of colour (see Feher and Meyer, 1992, as one example). One has only to watch an old black and white film on television to realise that colour plays a very important role in our lives.…”
Section: An Inquiry Into the Teaching Of Lightmentioning
confidence: 99%